2004
DOI: 10.2465/jmps.99.298
|View full text |Cite
|
Sign up to set email alerts
|

Sapphirine and corundum bearing ultrahigh temperature rocks from the Palghat-Cauvery Shear System, southern India

Abstract: We report a new occurrence of sapphirine and corundum bearing silica deficient Mg Al rocks from Paramati at the northern margin of the Palghat Cauvery Shear System which define the Archaean Proterozoic collisional boundary in southern India. Sapphirine here occurs as medium grained euhedral to subhedral crystals enclosed within plagioclase and contains inclusions of spinel and sillimanite, and is locally intergrown with corundum, suggesting the reaction Spl + Sil Spr + Crn. Temperatures estimated from sapphiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 21 publications
6
34
1
Order By: Relevance
“…1). Here, mafic to ultramafic rocks are often intercalated with corundum -, sapphirine -, and spinel -bearing Mg -Al -rich rocks (Santosh et al, 2004a;Koshimoto et al, 2004), suggesting that the package of all the lithologies underwent high -grade metamorphism. However, the field relation of the garnetclinopyroxene rock is not known as the garnet -rich layer is mostly covered by thick soil.…”
Section: Petrography and Mineral Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…1). Here, mafic to ultramafic rocks are often intercalated with corundum -, sapphirine -, and spinel -bearing Mg -Al -rich rocks (Santosh et al, 2004a;Koshimoto et al, 2004), suggesting that the package of all the lithologies underwent high -grade metamorphism. However, the field relation of the garnetclinopyroxene rock is not known as the garnet -rich layer is mostly covered by thick soil.…”
Section: Petrography and Mineral Chemistrymentioning
confidence: 99%
“…However, the field relation of the garnetclinopyroxene rock is not known as the garnet -rich layer is mostly covered by thick soil. Koshimoto et al (2004) estimated peak metamorphic temperature of 930 -950 °C and inferred clockwise P -T history. Mineral abbreviations discussed below are after Spear (1993).…”
Section: Petrography and Mineral Chemistrymentioning
confidence: 99%
“…Shimpo et al (2006) and Tsunogae and Santosh (2006) reported near eclogite facies high pressure (HP) metamorphism at P>12 kbar and following UHT peak event of T = 940 990 ºC from the PCSS, which is probably related to Neoproterozoic continent continent collision orogeny from this terrane. Available petrological data from adjacent areas along the PCSS also support such HP and UHT metamorphism (Tsunogae and Santosh, 2003;Koshimoto et al, 2004;Santosh and Sajeev, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this short report is to describe new occurrence and chemistry of extremely Na rich gedrite (~ 3.1 wt% Na 2 O) in Mg Al rich rocks from the northernmost flank of the Pan African Madurai Block along the Palghat Cauvery Shear Zone system (PCSS) in southern India. Such high Na gedrite has not been reported in previous studies from this area (cf., Koshimoto et al, 2004;Shimpo et al, 2006;Santosh and Sajeev, 2006) and from other UHT terranes. Shimpo et al (2006) and Tsunogae and Santosh (2006) reported near eclogite facies high pressure (HP) metamorphism at P>12 kbar and following UHT peak event of T = 940 990 ºC from the PCSS, which is probably related to Neoproterozoic continent continent collision orogeny from this terrane.…”
Section: Introductionmentioning
confidence: 99%
“…This is also regarded as the trace of the collisional suture of the Gondwana supercontinent during its final assembly in the Late Neoproterozoic to Early Cambrian (e.g., Chetty and Bhaskar Rao, 2006;Collins et al, 2007a). Recently, ultrahigh -temperature (UHT; T > 1000 °C at ~ 8 kbar) granulites have been reported from several localities in the northern MGB and PCSZ probably formed by deep subduction and subsequent continent -continent collision along this suture zone Koshimoto et al 2004;Shimpo et al, 2006;Sajeev, 2006: Collins et al, 2007b;Santosh, 2006a, 2007;Tsunogae et al, 2008a). However, only few studies on the role of fluids related to the UHT metamorphism have been carried out in this region.…”
Section: Introductionmentioning
confidence: 99%